Proceedings of the 1st Workshop on Interactive eXtended Reality 2022
DOI: 10.1145/3552483.3556460
|View full text |Cite
|
Sign up to set email alerts
|

Partially Reliable Transport Layer for QUICker Interactive Immersive Media Delivery

Abstract: Interactive immersive media come with stringent network-level requirements such as high bandwidth (i.e., several Gbps) and low latency (i.e., five milliseconds). Today, most video-streaming applications leverage the transmission control protocol (TCP) for reliable end-to-end transmission. However, the reliability of TCP comes at the cost of additional delay due to factors such as connection establishment, head-of-line (HOL) blocking, and retransmissions under sub-optimal network conditions. Such behavior can l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Unlike TCP, QUIC introduces streams on the transport layer, thereby making it aware of the streams being multiplexed on the application layer. The streams on the transport layer can be mapped to those on the application layer, which lets the transport layer process streams individually [7].…”
Section: B Http and Hol Blockingmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike TCP, QUIC introduces streams on the transport layer, thereby making it aware of the streams being multiplexed on the application layer. The streams on the transport layer can be mapped to those on the application layer, which lets the transport layer process streams individually [7].…”
Section: B Http and Hol Blockingmentioning
confidence: 99%
“…Moreover, the presence of reliability at the transport layer proves to be a performance bottleneck, especially for applications with lowlatency requirements. In our previous work, we have shown that not all applications require complete reliability at the transport layer [7]. This subsection provides an overview of related work in the domain of partially reliable data delivery.…”
Section: Quic and Partially Reliable Deliverymentioning
confidence: 99%
See 3 more Smart Citations